Macrocytosis, Macrocytic Anemia, and Genetic Polymorphisms of Alcohol Dehydrogenase‐1B and Aldehyde Dehydrogenase‐2 in Japanese Alcoholic Men. (3rd March 2014) - Yokoyama, Akira; Yokoyama, Tetsuji; Brooks, Philip J.; Mizukami, Takeshi; Matsui, Toshifumi; Kimura, Mitsuru; Matsushita, Sachio; Higuchi, Susumu; Maruyama, Katsuya
<x xml:space="preserve">Abstract</x> Background Oxidation of ethanol by alcohol dehydrogenase (ADH) generates acetaldehyde (AcH), which is converted to acetate by aldehyde dehydrogenase‐2 (ALDH2). Roughly 40% of East Asians are ALDH2‐deficient due to an inactive enzyme encoded by the ALDH2*2 allele. ALDH2‐deficient individuals have a dramatically elevated risk of esophageal cancer from alcohol consumption. Methods We investigated the relationship between ALDH2*2, ADH1B*2 (encoding a highly active ADH) and erythrocyte abnormalities, in a population of Japanese alcoholic men (N = 1, 238). Results Macrocytosis (mean corpuscular volume [MCV] ≥100 fl) and macrocytic anemia (MCV ≥100 fl and hemoglobin <13.5 g/dl) were found in 62.4 and 24.1% of the subjects, respectively. Age‐adjusted daily alcohol consumption did not differ according to ADH1B and ALDH2 genotypes. However, macrocytosis and macrocytic anemia were strongly associated with the ALDH2*1/*2 genotype multivariate odds ratios (ORs; 95% confidence interval [CI] = 2.85 [1.95 to 4.18] and 3.68 [2.64 to 5.15], respectively, versus ALDH2*1/*1). In comparison with the ADH1B*1/*1 and ALDH2*1/*1 genotype combination, the ADH1B*1/*1 and ALDH2*1/*2 genotype combination and the ADH1B*2 allele and ALDH2*1/*2 genotype combination increased stepwise the ORs (95% CI) for macrocytosis (1.65 [0.92 to 2.94] and 4.07 [2.33 to 7.11], respectively, p for difference in OR = 0.015) and macrocytic anemia (2.80 [1.52 to 5.15] and 5.32 [3.29 to 8.62], respectively, p for difference in OR = 0.045). Genotype effects were more prominent on the risks of the more advanced erythrocyte abnormalities. Older age, cigarette smoking, and low body mass index independently increased the risks of the erythrocyte abnormalities. Consumption of beer, which contains folate, decreased the risks, whereas consumption of alcoholic beverages lacking folate did not. Conclusions These results suggest that the erythrocyte abnormalities in alcoholics are attributable to high AcH exposure as well as to nutritional deficiencies and may be prevented by folate.